Usefulness of the LDL-C/apoB ratio in the overall evaluation of atherogenicity of lipid profile. (1st January 2017) - Kaneva, Anastasiya M; Potolitsyna, Natalya N; Bojko, Evgeny R
Abstract: Context : The ratio of low-density lipoprotein cholesterol to apolipoprotein-B (LDL-C/apoB) conventionally represents an alternative index of LDL particle size. Objective : This study was undertaken to determine the importance of LDL-C/apoB ratio in the overall evaluation of atherogenicity of lipid profile. Methods : The plasma levels of total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), apolipoprotein (apo) A-I, apoB and apoE were measured in 186 apparently healthy men using enzymatic and immunoturbidimetric methods. Results : The subjects with low values of the LDL-C/apoB ratio, indicating a predominance of small dense LDL (sd-LDL) particles in plasma, were characterized by higher TG levels and lower apoE levels. Conclusion : Low levels of apoE are most likely a cause of reduced clearance of TG-rich lipoproteins, which promotes the formation of sd-LDL. Determination of the LDL-C/apoB ratio can be used for monitoring qualitative changes in lipid profile, in addition to traditional lipid variables indicating quantitative changes.